Revisiting Work Culture: A Literature Based Analysis of Its Influence on Employee Performance - Nofiyanti Nofiyanti; Masduki Asbari; Andira Fajrin; Sefthian; Lorence Manalu; Winanti Winanti (Journal of Information Systems and Management (JISMA), 2025)
In today’s rapidly evolving business environment, organizational competitiveness is increasingly influenced by the quality of its human capital. Central to this is work culture, which serves as a foundation for promoting innovation, productivity, and employee well-being. This study adopts a qualitative literature review approach to examine how work culture affects employee performance. The analysis synthesizes findings from scholarly sources published within the last decade to ensure relevance and rigor. Results reveal that a strong and positive work culture characterized by open communication, mutual respect, ethical values, and managerial support—significantly contributes to individual and team performance. Moreover, cultural elements such as selfefficacy, motivation, fair workload distribution, and a supportive work environment mediate the relationship between organizational values and employee outcomes. These insights affirm the necessity of fostering a collaborative, values-driven workplace culture as a strategic imperative for sustainable organizational success.